Integration of Traditional and Western Medicine treatment benefits to lupus nephritis disease: a systematic review and meta-analysis - yang, Meng (Journal of Medical Biomedical and Applied Sciences, 2017)
Objectiveï¼To systematically evaluate the clinical effect of integrated traditional Chinese medicine and Western Medicine (TCM-WM) and to investigate effective therapy of traditional Chinese medicine (TCM ) for lupus nephritis(LN). Methods A meta-analysis      was performed of all the literatures  germane  to estimate the patients treated with TCM-WM and western medicine(WM ) alone from published randomised controlled trials (RCTs) from 1990 to 2013. Results 12 RCTs were included. The methodological quality was generally low. The complete remission rate(RR =1.68, 95%CI 1.48-1.90, P<0.00001) and the total remission rate(RR =1.19, 95%CI 1.13-1.24, P<0.00001) of TCM-WM were higher than that of WM .The relapse rate(RR =0.3, 95%CI 0.22-0.42, P<0.00001), incidence of adverse reactions (RR =0.46, 95%CI 0.40-0.54, P<0.00001)and mortality rate (RR =0.38, 95%CI 0.23-0.63, P=0.00002)  of  TCM-WM were much lower than WM.  Conclusion  Our results indicate that using improving the blood flow clearing away toxic material, activating blood circulation to dissipate as central TCM-WM therapy were superior to therapy with WM alone. However, its effect on LN requires further careful study due to limited available randomized control trials.